DAMPAK PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS X MAN KOTA SOLOK - Haniva Aini; Budi Juliardi; Azwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the impact of TikTok social media use on students' learning motivation in the Pancasila Education subject among tenth-grade students at MAN Kota Solok. This research employed a quantitative approach using an ex post facto design. The population consisted of 208 students, while 52 students were selected as the sample through simple random sampling. Data were collected using a questionnaire and analyzed through descriptive statistics, normality testing, simple linear regression, the coefficient of determination, and the t-test using SPSS version 22. The findings revealed that TikTok social media use has a positive and significant effect on students' learning motivation, as indicated by a significance value of 0.016 (<0.05) and a regression coefficient of 0.426. The coefficient of determination was 11%, indicating that TikTok use contributed to students' learning motivation, while the remaining 89% was influenced by other factors beyond the scope of this study. Therefore, the appropriate and educational use of TikTok can serve as a supporting medium for enhancing students' learning motivation in Pancasila Education.